Current state of data stewardship tools in life science - Aksenova, Anna; Johny, Anoop; Adams, Tim; Gribbon, Phil; Jacobs, Marc; Hofmann-Apitius, Martin (Frontiers in Big Data, 2024)
In today's data-centric landscape, effective data stewardship is critical for facilitating scientific research and innovation. This article provides an overview of essential tools and frameworks for modern data stewardship practices. Over 300 tools were analyzed in this study based on their description in the literature. We are assessing their utility, relevance to data stewardship, and applicability within the life sciences domain.